(untitled) (Research, Society and Development, 2023)
Cataracts are a common eye disease and remain the leading cause of reversible blindness worldwide. Until a few years ago, cataract surgery was indicated only after a very pronounced loss of vision. With the evolution of technology and the advent of phacoemulsification, the indication for this surgery is increasingly earlier. However, it continues to present challenges and risks. Intraocular manipulation, such as that occurring during phacoemulsification cataract surgery, causes fluid turbulence and lens fragments, which can lead to endothelial damage, resulting in transient impairment of function or permanent cell loss. The present study aims to evaluate the loss of endothelial cells, and their impact, in patients undergoing cataract surgery. This is a narrative review, where the number of endothelial cells and corneal thickness will be compared, before and after phacoemulsification cataract surgery. More than 20 articles will be used, with their data systematically analyzed and compared. It is expected that the factors most commonly associated with greater endothelial losses and possible visual disorders will be elucidated, as well as the safety assessment of cataract surgery nowadays.